Long‐term risk of arch complications in Loeys Dietz syndrome patients undergoing proximal ascending aortic replacement. Issue 11 (21st August 2022) - Weininger, Gabe; Zafar, Mohammad; Ziganshin, Bulat A.; Mori, Makoto; Papanikolaou, Dimitra; Sekar, Rajesh B.; Amabile, Andrea; Degife, Ellelan; O'Marr, Jamieson; Geirsson, Arnar; Elefteriades, John A.; Assi, Roland; et al.
Abstract: Purpose: Loeys‐Dietz syndrome (LDS) is a rare connective tissue disorder. In LDS patients with normal arch morphology, whether the arch should be prophylactically replaced at the time of proximal aortic replacement remains unknown. We evaluated the risk of long‐term arch complications in genetically confirmed LDS patients who underwent proximal ascending aortic replacement. Methods: We retrospectively reviewed the records of patients with LDS who have been followed at our institution between 1994 and 2020. Patients were only included if whole exome genetic testing confirmed a mutation in an LDS‐causing gene ( TGFBR1, TGFBR2, SMAD3, TGFB2, or TGFB3 ). Mutations were categorized as pathogenic, benign, or of unknown significance. We collected demographic information, aortic dimensions, comorbidities, mortality, and operative course from patients' charts. Descriptive statistics and freedom from reoperation plots were generated. Results: Of the 18 patients with a mutation in an LDS‐causing gene, 15 had known pathogenic variants, two had mutations of unknown significance, and one had a benign genetic variant. For the 15 patients with confirmed pathogenic variants of LDS the median follow‐up duration was 5 years (interquartile range [IQR]: 4–8). Eleven patients underwent ascending aortic replacements (AAR) ± aortic valve replacement. Two patients required an additional operation; one required arch and staged elephant trunk for a dissection 18 years post‐AAR and the other patient required an isolated descending aortic replacement for dissection 5 years post‐AAR. Among patients who underwent surgery, the median ascending aortic diameter at intervention was 5.0 cm (IQR: 4.3–5.3). There was no surgical or late follow‐up mortality observed for any of the 18 patients in the study. Conclusion: LDS patients who underwent proximal aortic replacement appeared to have low long‐term risk of arch complications. While our study is somewhat limited by its sample size and follow‐up duration, it suggests that routine prophylactic total arch replacement may not be warranted in LDS patients with nonaneurysmal aortic arches.